ASP.NET MVC 5 Identity: Authentication and Authorization. - Trupja, Ervis (linkedin.com, 2018)
Learn how to authenticate and authorize users of your ASP.NET MVC 5 application using login credentials from Facebook, Twitter, Google, Microsoft, and other third-party providers.